Evaluasi Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Di SMP Negeri - Devina Putri Faradhiba; Nurul Latifatul Inayati (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
This research was made to find out the process of implementing the evaluation of Islamic religious education and morals in junior high school 1 Ngariboyo Magetan through the interview method. The theoretical basis used is based on the theory of learning evaluation, such as Bloom's taxonomy and other learning evaluation theories. Things discussed around the evaluation of Islamic religious education and morals include preparation of learning evaluations, assessment lists, daily grades, and written and oral exams. The obstacle in undergoing a learning evaluation is the limited teaching staff for Islamic religious education at this school, so the teaching staff needs to use a more effective and efficient way of conducting learning evaluations consisting of 21 class groups, with details for each class level there are 7 classes, there are also other obstacles that are obtained, namely the uneven understanding of students so that in preparing learning evaluations it is necessary to evaluate learning according to student’s abilities. Whereas the assessment standards are made according to the average ability of students, for students who have not been able to meet the assessment standards, a reassessment will be carried out.